基于某柴电商用车的电控离合器的接合过程分析研究 - 岳宏超; 李守成; 吴海啸 (Jixie chuandong)
By analyzing the structure of a diesel-electric hybrid commercial vehicle and the dynamic model of the automatic clutch,the engaging process of automatic clutch is studied from the vehicle normal start and big initial slope start.Based on analyzing the control strategy,the test is carried out with dSPACE rapid control prototype tool.The results show that the control strategy of automatic clutch can not only guarantee the rapid state-switching,but also meet the special requirements of big initial slope start.